Odpowiedzi

Najlepsza Odpowiedź!
2009-11-26T16:30:01+01:00
A) (x+1)(x+2)= x²+2x+x+2=x²3x+2
b) (3a+4)(a-5)=3a²-15a+4a-20=3a²-11a-20
c) (2t+1)(1-3t)=2t-5t²+1-3t=-t-5t²+1
d) (3ab-7)(3-7ab)=6ab-21ab²-21+49ab=50ab-21ab²-21
e) (x-y)(5x+6y)=5x²+6xy-5xy-6y²=5x²+xy-6y²
f) (x+5y)(7x-y)=7x²-xy+35xy-5y²=7x²+34xy-5y²

Proszę ;)
1 5 1
2009-11-26T16:33:09+01:00
A) (x+1)(x+2)=x²+2x+x+2=x²+3x+2
b) (3a+4)(a-5)=3a²-15a+4a-20=3a²-11a-20
c)(2t+1)(1-3t)=2t-6t²+1-3t=-t-6t²+1
d) (3ab-7)(3-7ab)=9ab-21a²b²-21+49ab=58ab-21a²b²-21
e) (x-y)(5x+6y)=5x²+6yx-5yx-6y²=5x²+xy-6y²
f) (x+5y)(7x-y)=7x²-xy+35xy-5y²= 7x²+34xy-5y²
1 5 1